Pembajakan Di Laut Yang Dilakukan Secara Bersama-Sama Di Provinsi Lampung - Zainab Ompu Jainah; Cintya Dwi Meilita C (Widya Yuridika, 2022)
The crime of piracy at sea often causes losses for ship owners. The pirates even kidnapped the captain of the ship, the crew, and the ship did not escape their targets. This aims to extort the ship owners so that they give money in a certain nominal which causes these pirates to benefit. The problems found in this study are how the judges' basic considerations in making decisions against perpetrators of criminal acts participating in piracy at sea and what are the factors that cause perpetrators to commit criminal acts of participating in piracy at sea based on Decision Number 443/Pid.B/2021/ PN.Tjk? The results of this study are the basis for judges' considerations in making decisions against perpetrators of criminal acts of participating in piracy on the sea, namely legal facts that were revealed in court, both juridical and non-juridical aspects, while the factors that caused perpetrators to commit crimes were participating in piracy above. marine factors include educational factors, individual factors, economic factors, environmental factors, the low level of criminal sanctions imposed, and global development factors